Corruption and Its Impact on Social Counseling in Society - YAQIN, Mohammad Nurul (Integration: Journal Of Social Sciences And Culture, 2024)
Purpose:Corruption is a social problem that has a significant impact on various aspects of life, including social counseling services. Abuse of power practices, such as embezzlement, nepotism, and low levels of transparency, result in reduced access and quality of services for individuals in need of psychosocial assistance. This study aims to examine how corruption can hinder the effectiveness of social counseling services, reduce the professionalism of counselors, and erode public trust in social institutions.Methodology:Using a literature study method and a qualitative approach, this study analyzes the impact of corruption on the success of counseling programs and strategies that can be implemented to increase transparency and accountability in this sector.Findings:The results of the study indicate that reform of the supervisory system, strict law enforcement, and increased community participation are key steps to minimize the impact of corruption on social counseling services.Implication:Corruption in social counseling services has a very broad impact on community welfare, both in terms of accessibility, quality of service, and public trust in social institutions. Public distrust of social institutions due to corruption also reduces their participation in assistance programs, thus widening social inequality.